KONTRIBUSI PENERIMAAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN ACEH TENGAH (2013-2017) - Munawardi Munawardi; Nur Aidar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
Abstract This research aims to find out how much the contribution of the local levy to the income revenue of Central Aceh district. By using regional retribution variables and income revenue regions. The method used in the study is a quantitative descriptive method by using secondary data from 2013 to 2017 . Results showed that the contribution of regional retribution to the PAD Aceh Central is very positive even though it is relatively small. But However the contributions can still be improved as the improvement of the community's economic development. The biggest contribution was seen in 2013 by 9.51 percent. Furthermore, the contribution was continuing to decline until the year 2017, where it contributed to 3.43 percent. This contribution is relatively low compared to the target of the regional levy of 2017 which is 6.91 percent or 12 billion, where it s only achieved 5.5 billion. The Government for the future is expected to socialize the importance of regional retribution and also continuously control the system of retributionKeywords: Regional Retribution, Regional Original Revenue and regional autonomy